Atroposelective desymmetrization of 2-arylresorcinols via Tsuji-Trost allylation - Sangji Kim; Aram Kim; Chanhee Lee; Junsoo Moon; Eun Jeong Hong; Duck-Hyung Lee; Yongseok Kwon (Communications Chemistry, 2023)
Desymmetrization of symmetric biaryls is an efficient but underexplored way to approach axially chiral molecules. Here, the authors report the atroposelective desymmetrization of 2- arylresorcinols via chiral palladium complex-catalyzed allylic alkylation.